Autonomie und Struktur in Selbstlernarchitekturen Empirische Untersuchung zur Dynamik von Selbstlernprozessen - Maier Reinhard, Christiane (Beiträge der Schweizer Bildungsforschung, 2008)
The authors examine the form and dynamics of self-learning processes within the institutional contexts of professionalization in teacher education.